Level of Maturity Regional Innovation System as an Effort Improving Public Services - Hidayat, Bachtari Alam; Akbar, Alexander; Faturohim, Agus (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Regional innovation system is related to the entire process of developing innovation between government institutions, research institutions, business entities, and the community that prioritizes science, technology, and the development of new methods. The purpose of this research is to identify and analyze the types and groups as well as the maturity of regional innovations in the city of Palembang and include them in the regional innovation map. The data collection method used was interview with relevant stakeholders, such as government officials, academics, and practitioners involved in the development of regional innovations and public services. Observation, which is a method of collecting data by making direct observations on regional innovation systems and public services in a number of selected regions. Questionnaire, which is a method of collecting data using questionnaires filled out by a number of related respondents, such as government employees and communities involved in or receiving public services in the area studied. The results of this study show that the regional innovation development roadmap for the city of Palembang until 2019 has totaled 126 innovations issued by the regional organization (OPD), but there are still many programs that are at the initiation stage so efforts are needed to develop infrastructure, human resources, regional funding to policies capable of making innovations run sustainable. Efforts to accelerate the implementation of governance reforms in the regions need to be encouraged through innovation programs for all regional government administration affairs. Therefore, the development and implementation of innovation in the regions is not only limited to the internal bureaucracy, but also must be encouraged to the private sector and the community which is expected to increase regional competitiveness.